Nonuniform muscle hypertrophy along the length induced by resistance training - Wakahara, T. (Sports Performance, 2015)
Resistance training induces an increase in skeletal muscle size (hypertrophy). This hypertrophy can occur nonuniformly along the length of a muscle or muscle group. This review summarizes studies examining training-induced hypertrophy in multiple regions of human skeletal muscles. Results showed highly variable hypertrophic patterns along the length of muscle(s), possibly due to disparities in training programs and subject characteristics. Although differences in muscle activation and contractile protein synthesis are associated with such nonuniform hypertrophic change, the underlying mechanisms remain unclear. Future investigations are needed to reveal the mechanisms and to design resistance training programs that consider region-specific muscle hypertrophy.